2014
DOI: 10.1371/journal.pone.0087052
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Area and Membrane Folding in Glioblastoma Cell Lines Differing in PTEN and p53 Status

Abstract: Glioblastoma multiforme (GBM) is characterized by rapid growth, invasion and resistance to chemo−/radiotherapy. The complex cell surface morphology with abundant membrane folds, microvilli, filopodia and other membrane extensions is believed to contribute to the highly invasive behavior and therapy resistance of GBM cells. The present study addresses the mechanisms leading to the excessive cell membrane area in five GBM lines differing in mutational status for PTEN and p53. In addition to scanning electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 65 publications
(85 reference statements)
1
33
0
Order By: Relevance
“…Although derived from the same tumor entity, the 2 glioblastoma multiforme (GBM) cell lines used in this study, DK-MG and SNB19, differ markedly in the mutational status of the most prominent tumor suppressors PTEN and p53 (40). Both genes are wild type in DK-MG cells, whereas in the SNB19 cell line, both genes are mutated.…”
Section: Resultsmentioning
confidence: 99%
“…Although derived from the same tumor entity, the 2 glioblastoma multiforme (GBM) cell lines used in this study, DK-MG and SNB19, differ markedly in the mutational status of the most prominent tumor suppressors PTEN and p53 (40). Both genes are wild type in DK-MG cells, whereas in the SNB19 cell line, both genes are mutated.…”
Section: Resultsmentioning
confidence: 99%
“…Glioblastoma cells have a complex actin cytoskeleton-related cell surface morphology with abundant membrane folds, microvilli, and filopodia, which play a role in its invasive phenotype. 3 Cell migration begins with polymerization of actin filaments and extending lamellipodia and filopodia protrusions of the cell membrane. 4 Protrusions are stabilized by focal adhesions and actin cytoskeleton in the form of stress fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Diamond nanoparticles (ND), graphite nanoparticles (NG), and graphene oxide nanoplatelets (nGO) are carbon allotropes that, although similar in size, have different physical properties. ND has carbon atoms in sp 3 hybridization, whereas NG and nGO have carbon atoms in the sp 2 hexagonal pattern. However, nGO has a unique thickness to surface area ratio, which distinguishes this material from both ND and NG.…”
Section: Introductionmentioning
confidence: 99%
“…Memme et al. discussed the increased membrane area and folding in mutant glioblastoma multiforme (GBM) lines, suggesting that it may be related to enhanced protein and lipid synthesis due to a deregulation of the mTOR dependent downstream signalling pathway. It has been observed that the difference in crossover frequency between the blood cells and the CTCs relies on the morphology of the cellular membrane .…”
Section: What Makes Dielectrophoresis a Methods Of Choice For Ctcs Isomentioning
confidence: 99%
“…Memmel et al. demonstrated in glioblastoma cells that modulation of PTEN and p53 affected the cell size and membrane synthesis of cells via deregulation of the PI3K/AKT/mTOR pathway . However, the correlation of cell dielectric phenotype with molecular pathways that impact membrane morphology should be further studied.…”
Section: The Future Of Dielctrophoretic Isolation and Characterizatiomentioning
confidence: 99%